Associations of Physician Supplies With Breast Cancer Stage at Diagnosis and Survival in Ontario, 1988 to 2006 - Gorey, Kevin M. (2009)
BACKGROUND: The authors examined whether the supply of primary care physicians had protective effects on breast cancer stage and survival in Ontario and whether supply losses during the 1990s were associated with diminished protection. METHODS: Random samples of the Ontario Cancer Registry, respectively, provided 879 women and 951 women who were diagnosed with breast cancer between 1988 and 1990 (followed until 1996) and 1998 and 2000 (followed until 2006), respectively. Active physician supply data (1991 and 2001) joined to each woman’s census division of residence was taken from the Scott’s Medical Database. RESULTS: Protective thresholds were observed among the earlier cohort for supplies of general practitioners (7 per 10,000 population) and supplies of obstetricians/gynecologists (6 per 100,000 population) at or above which women with breast cancer were significantly more likely to have been diagnosed with localized disease and to have survived for ≥5 years. These protective effects seemed generally attenuated among the more recent cohort. The risk of living in primary care physician-undersupplied areas increased significantly between 1991 and 2001 (10%–30%), and such physician supply losses were associated with reduced cancer care protection, including less prevalent early diagnoses (odds ratio [OR], 1.60; 95% confidence interval [95% CI], 1.00–2.58) and lower 5-year survival rates (OR, 1.62; 95% CI, 1.03–2.55). CONCLUSIONS: Primary care physician supplies appeared to matter very much in the effective provision of cancer care in Canada. Community healthcare service endowments that include adequate physician supplies may be particularly critical to the performance of a healthcare system such as that in Canada, which provides universal accessibility to medically necessary care.